Perspektif Hukum Islam Tentang Tradisi Muang Cangcalah Bagi Masyarakat Karanganyar Kecamatan Bantaran - Rizal, Saiful; Rusly, Fathullah; Yuliardy Nugroho, Irzak (Muhammadiyah University of Surabaya, 2025)
This study discusses the Muang Cangcalah tradition carried out by the Karanganyar community, Probolinggo, as a response to death. This study uses a qualitative method in data collection. The tradition reflects social values such as empathy, solidarity, and preservation of local culture. From the perspective of Islamic law, this tradition can be categorized as ‘urf sahih as long as it is not accompanied by the belief that objects such as small change, coins, or yellow rice have supernatural powers to ward off disaster independently. As long as this practice is based on a straight intention and does not deviate from the creed of monotheism, then it does not conflict with Islamic law. However, if there are elements of belief that lead to shirk, guidance is needed to straighten out the community's understanding. This study recommends an educational approach in responding to this kind of tradition in order to maintain a balance between cultural preservation and the purity of Islamic creed. Keywords: Islamic Law, Muang Cangcalah, ‘Urf